2013
DOI: 10.1007/978-3-642-40069-8_2
|View full text |Cite
|
Sign up to set email alerts
|

Self-stabilizing Consensus Average Algorithm in Distributed Sensor Networks

Abstract: Abstract. One important issue in sensor networks that has received renewed interest recently is average consensus, i.e., computing the average of n sensor measurements, where nodes iteratively exchange data with their neighbors and update their own data accordingly until reaching convergence to the right parameters estimate. In this paper, we introduce an efficient self-stabilizing algorithm to achieve/ensure the convergence of node states to the average of the initial measurements of the network. We prove tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…More precisely, the information exchange between nodes involves only the connected dominating set (CDS) of the network graph to reduce the sensors' overall power consumption. [4] developed a novel approach using self stabilization under a serial daemon scheduler. It was shown that the proposed algorithm converges in a linear time complexity with a tighter bound of the global equilibrium threshold.…”
Section: Literature Reviewmentioning
confidence: 99%
“…More precisely, the information exchange between nodes involves only the connected dominating set (CDS) of the network graph to reduce the sensors' overall power consumption. [4] developed a novel approach using self stabilization under a serial daemon scheduler. It was shown that the proposed algorithm converges in a linear time complexity with a tighter bound of the global equilibrium threshold.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This approach often proves to be the most effective solution when there is a lack of global information about the topology of a network. This applies to a range of possible networks, ad‐hoc, wireless sensor, and so on, so the approach has attracted a significant amount of attention …”
Section: Introductionmentioning
confidence: 99%
“…This applies to a range of possible networks, ad-hoc, wireless sensor, and so on, so the approach has attracted a significant amount of attention. [2][3][4][5][6][7][8] The advantage of self-stabilization algorithms lies in their elegance and simplicity. However, this comes at a cost.…”
mentioning
confidence: 99%